PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH MELALUI FASILITASI USAHA PEMBUATAN DUPA - Sari, Novi Primita (Studi Kasus Inovasi Ekonomi, 2019)
Development of Micro, Small and Medium Enterprises (MSMEs) Through Incense Manufacturing Business Facilities (Case Study in Gondang Tegalgondo Village, Karangploso, Malang District). Internal development efforts from household entrepreneurs that produce output in the form of incense to increase potential by using initial capital with their own savings. However, because this business is still a small household business, there are several constraints, including limited human resources, lack of facilities and infrastructure to support production, and packaging of incense products as well as low knowledge about entrepreneurship, resulting in no increase in economic value due to market share the destination is still around Bali and surrounding Malang. The solutions offered to partners are counseling and socialization and discussion with partners. The result of the discussion was that partners began to understand production management efficiently by involving technologies such as incense drying tools that were still being processed, so that even though the rainy season could still produce, partners also got the knowledge that the importance of providing trade name labels related to incense was produced to add value economical on goods produced.